Integrative Single‐Cell Analysis Reveals Iron Overload‐Induced Senescence and Metabolic Reprogramming in Ovarian Endometriosis‐Associated Infertility - Yangshuo Li; Wei Zhou; Jie Ding; Di Song; Wen Cheng; Jin Yu; Shuai Sun; Shanshan Mei; Xiaolan Liang; Qianqian Zhao; Yanping Kuang; Mingqing Li; et al. (Advanced Science)
Abstract Endometriosis, particularly ovarian endometriosis (OE), is a major cause of infertility, often associated with reduced oocyte quality and impaired ovarian function. Iron overload plays a key role in OE progression. This study investigates the effects of iron overload on follicular function in OE‐associated infertility (OEI). A single‐cell atlas of pre‐ovulatory follicular fluid from OEI patients reveals dynamic changes in iron metabolism and iron‐induced senescence phenotypes. Spatial transcriptomics using Stereo‐seq in iron‐overloaded mouse ovaries further identifies localized senescence features. Additional analysis of aging human ovaries highlights conserved patterns of iron dysregulation. These findings provide mechanistic insight into iron overload‐related ovarian pathology and suggest potential therapeutic targets for improving oocyte quality in OEI.